1995
DOI: 10.1177/01461672952112005
|View full text |Cite
|
Sign up to set email alerts
|

Self-Evaluation Processes

Abstract: Four motives (self-assessment, self-enhancement, self-verification, and self-improvement) are hypothesized to guide self-evaluation. Results of an empirical investigation suggest that two sets of circumstances may commonly elicit all four motives: a situation of past threat or failure and anticipation of some important future threat or challenge. These findings suggest the need to develop an integrative approach to self-evaluation that specifies not only the distinctive circumstances in which each motive may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
171
0
6

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(181 citation statements)
references
References 27 publications
4
171
0
6
Order By: Relevance
“…Taylor et al (1995) found that evaluations of the past primarily serve purposes of selfenhancement and self-assessment and that evaluations of the future predominantly support the quest for self-improvement. For selfenhancement and self-improvement to be adaptive, they should both follow the rule of the optimal margin of illusion to be functional (e.g., Baumeister, 1989;Staudinger & Pasupathi, 2000).…”
Section: Diachronicity Across the Life Spanmentioning
confidence: 96%
“…Taylor et al (1995) found that evaluations of the past primarily serve purposes of selfenhancement and self-assessment and that evaluations of the future predominantly support the quest for self-improvement. For selfenhancement and self-improvement to be adaptive, they should both follow the rule of the optimal margin of illusion to be functional (e.g., Baumeister, 1989;Staudinger & Pasupathi, 2000).…”
Section: Diachronicity Across the Life Spanmentioning
confidence: 96%
“…Social comparisons may thus be used to generate information, which serve the assessment and verification of one's abilities, the enhancement and maintenance of a positive sense of the self, as well as the improvement of specific skills. Taylor et al (1995) also point out that more than one self-evaluative motive may be present in a given situation exerting an influence on information processing underlying comparison activity.…”
Section: Motives Directions and Effects Of Social Comparisonsmentioning
confidence: 97%
“…Taylor 1983;Taylor et al 1995; for an overview see Buunk and Gibbons 2007). Taylor et al (1995) assume four motives directing selfevaluation by social comparisons: Self-assessment serving the need to obtain accurate information about oneself when no objective standards are available, which is in line with the motive already postulated by Festinger; self-enhancement as the motive to achieve and maintain a positive sense of self; self-verification as the need to confirm existing cognitions about oneself, and finally self-improvement, being defined as the need to achieve improvement in specific skills. Social comparisons may thus be used to generate information, which serve the assessment and verification of one's abilities, the enhancement and maintenance of a positive sense of the self, as well as the improvement of specific skills.…”
Section: Motives Directions and Effects Of Social Comparisonsmentioning
confidence: 99%
“…Feedback may include verbal and non-verbal cues from others, success or failure on tasks, or social comparisons. Self-view maintenance is Attachment and feedback-seeking 6 motivated: People seek feedback frequently in everyday life (Taylor, Neter, & Wayment, 1995). Given that one's attachment orientation influences the areas from which one derives self-worth, it might also influence the feedback one seeks about those areas.…”
Section: Attachment and Feedback-seekingmentioning
confidence: 99%